Re-epithelialization: a key element in tracheal tissue engineering. (November 2015) - Zhang, Hengyi; Fu, Wei; Xu, Zhiwei
Trachea-tissue engineering is a thriving new field in regenerative medicine that is reaching maturity and yielding numerous promising results. In view of the crucial role that the epithelium plays in the trachea, re-epithelialization of tracheal substitutes has gradually emerged as the focus of studies in tissue-engineered trachea. Recent progress in our understanding of stem cell biology, growth factor interactions and transplantation immunobiology offer the prospect of optimization of a tissue-engineered tracheal epithelium. In addition, advances in cell culture technology and successful applications of clinical transplantation are opening up new avenues for the construction of a tissue-engineered tracheal epithelium. Therefore, this review summarizes current advances, unresolved obstacles and future directions in the reconstruction of a tissue-engineered tracheal epithelium.